Trans-cinnamaldehyde mitigates rotenone-induced neurotoxicity via inhibiting oxidative stress in rats - Sandeep Kumar; Sachin Kumar; Richmond Arthur; Puneet Kumar (Elsevier, 2023)
Background: The second most prevalent age-related brain condition, Parkinson's disease (PD) is characterised by the loss of neurons in the substantia nigra pars compacta (SNpc). It is associated with symptoms like bradykinesia, stiffness, tremor, and impaired postural responses. Motor dysfunction, and neurochemical imbalance, are involved in the pathophysiology of PD. It has been hypothesised that trans cinnamaldehyde (TCA) a component of Traditional Chinese Medicine (TCM) can ameliorate Parkinson-like symptoms by altering the levels of different biochemical markers and reverse motor impairments. This research sought to determine the neuroprotective effect of TCA against the neurotoxicity caused by rotenone. Basic Procedure: Rotenone (1.5 mg/kg/day; s.c. for 35 days) was given to rats to induce Parkinson-like symptoms. TCA (5, 10, and 20 mg/kg) and concomitant treatment of TCA (5 mg/kg) with L-NAME (10 mg/kg) were given one hour prior to rotenone administration. Every week until the 35th day, behavioral parameters (muscle coordination, spontaneous motor movement and gait abnormalities) were assessed using rotarod, actophotometer, and narrow beam apparatus respectfully. Rats were decapitated on the 35th day, the striatum and cortex were isolated for biochemical tests. Main findings: Rotenone treatment reduced body weight, altered motor coordination and reduced the oxidative defense system. Treatment with TCA significantly improved the alterations in antioxidant levels as well as behavioral parameters. Furthermore, L-NAME (nitric oxide synthase inhibitor) in combination with TCA had a more significant effect as compared to TCA alone, signifying a possible drug interaction. Principal conclusion: TCA could be employed as an adjuvant in PD management.